OPTIMALISASI MATERI DAN KOMPETENSI MATA KULIAH KEPERAWATAN BENCANA PADA AKADEMI KEPERAWATAN (Studi Kasus di Kota Banda Aceh dan Kabupaten Aceh Besar) - Fauzan, Mudatsir, T. Budi Aulia. (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2015)
Abstract: This study aimed to identify and optimize the materials and competencies of disaster nursing courses Nursing Academies in Banda Aceh City and Aceh Besar Regency. The research design of this study was descriptive study with qualitative methods by including 28 informants, consisted of 12 lecturers, 8 active students and 8 alumni. The sampling was taken by using non-probability sampling, with purposive sampling technique. Data were collected from December 24, 2014 to January 21, 2015 by using observation documen and focus group discussion (FGD). The data were analyzed by using the methodological triangulation and source triangulation technique. The results of this study identified the materials and competencies of disaster nursing courses implemented, which were: 1) The materials and competencies about disaster concept included: Basic disaster concept, Disaster management concept, and any efforts from government in avoiding, reducing, and over coming disaster impact along with the readiness and capability of personnel to face disaster. 2) The materials and competencies about disaster nursing concept included: Special (risky) group nursing, Mental health problem, Community nursing for each cycle of disaster, Preparing volunteers, International humanitarian aids and Red Cross for disaster, and first aid practices for disaster. The optimization of materials and competencies of disaster nursing courses could be done by including the concept of indigenous knowledge society, information and communication in disaster preparedness, health promotion and disaster education, and pre-hospital nursing in handling disaster victims. The content and learning sources for disaster nursing courses at Nursing Academies in Banda Aceh City and Aceh Besar Regency were still limited so that it needed to be developed in order to fit in the competency goals.Keywords: Course Material, Competency, Nursing, Disaster. Abstrak: Penelitian ini bertujuan mengidentifikasi dan mengoptimalkan materi dan kompetensi mata kuliah keperawatan bencana pada Akper di Kota Banda Aceh dan Kabupaten Aceh Besar. Desain penelitian deskriptif dengan metode kualitatif melibatkan informan sebanyak 28 orang, terdiri dari dosen pengajar, mahasiswa aktif dan alumni. Pengambilan sampel secara non probability sampling, menggunakan teknik purposive sampling. Pengumpulan data melalui observasi dokumentasi dan Focus Group Discussion (FGD). Data dianalisis dengan teknik triangulasi metode dan triangulasi sumber. Hasil penelitian telah mengidentifikasi materi dan kompetensi mata kuliah yang telah diterapkan, yaitu; 1) Materi dan kompetensi tentang konsep bencana, meliputi; Konsep dasar bencana, Konsep manajemen bencana, dan Berbagai upaya pemerintah dalam mencegah, mengurangi, dan menangani dampak bencana serta kesiapan dan kemampuan petugas pada bencana. 2) Materi dan kompetensi tentang konsep keperawatan bencana, meliputi; Perbedaan keperawatan kegawatdaruratan dengan keperawatan bencana, Keperawatan kelompok khusus (beresiko), Masalah kesehatan mental, Keperawatan komunitas setiap siklus bencana, Mempersiapkan tenaga relawan, bantuan kemanusiaan internasional dan PMI pada bencana, dan Praktek pertolongan pertama saat bencana. Optimalisasi materi dan kompetensi dengan memasukkan konsep pengetahuan dan kearifan lokal masyarakat, informasi dan komunikasi dalam keadaan bencana, promosi kesehatan dan pendidikan kebencanaan, serta keperawatan pre hospital penanganan korban bencana. Isi materi dan sumber referensi pembelajaran mata kuliah keperawatan bencana pada Akper di Kota Banda Aceh dan Kabupaten Aceh Besar masih sangat terbatas sehingga masih perlu dikembangkan agar sesuai dengan tujuan kompetensi.Kata Kunci : Materi Mata Kuliah, Kompetensi, Keperawatan, Bencana.